FACTIBILIDAD TÉCNICA-ECONÓMICA Y AMBIENTAL DE UN PARQUE EÓLICO OFFSHORE EN LA CIUDAD DE SALINAS - MORA VILLANUEVA , JHON WILLIAM (2025)
The project analyzes the technical-economic and environmental feasibility of an offshore wind farm in Salinas, Ecuador. The study addresses the climatic, technical and environmental challenges associated with the installation and operation of this energy infrastructure in a marine environment